The Public Service Alliance of Canada : A Look at a Union in the Public Sector - Boivin, Jean (Relations Industrielles / Industrial Relations, 1980)
This article reviews the book, "The Public Service Alliance of Canada : A Look at a Union in the Public Sector," by Maurice Lemelin.

The Shrinking Perimeter - Boivin, Jean (Relations Industrielles / Industrial Relations, 1980)
This article reviews the book, "The Shrinking Perimeter," by Hervey A. Juris & Myron Roomkin, Edited.

Deux systèmes de relations industrielles en Belgique - Boivin, Jean (Relations Industrielles / Industrial Relations, 1980)
This article reviews the book, "Deux systèmes de relations industrielles en Belgique," by Thérèse Klein-Beaupain.